A Model for Assessing the Quality of Marketing-Management Education - Rivera Camino, Jaime Eduardo (2015)
This study proposes and tests a model of educational quality in marketing management incorporating resource-capability variables linked to learning outcomes for students and the competitive positioning of universities. Drawing on resource-dependence theory, the study develops a comprehensive model for measuring educational quality. The hypothesised relationships in the model are tested with a sample of Spanish university teachers using a two-stage least squares regression analysis, while controlling for the possible effect of the public/private nature of the university. The results validate the model and show that educational capabilities are reliable variables for predicting the educational quality of marketing-management programs at Spanish universities. As with all educational research, certain problems are acknowledged with respect to the data and the theoretical constructs that are utilised in the study. Future studies could replicate this study using more direct objective measures of the theoretical constructs and extend the study to other countries with different educational contexts. This is one of the few studies to apply resource-dependence theory to an analysis of the variables associated with the quality of marketing-management education. In doing so, the study presents original multi-item scales to improve the measurement of model constructs. The results provide guidance to university marketing teachers in designing high-quality marketing-management educational programs and in developing self-diagnostic tools that determine a university’s likelihood of competitive success.